MASALAH LINGKUNGAN HIDUP INDONESIA MENGHADAPI ERA GLOBALISASI - Rusdiyanto, Rusdiyanto (Jurnal Cakrawala Hukum, 2017)
In a global dimension, Indonesia is part of global society itself. Geographically Indonesia become strategic aspart of good enviromental embodiment. It is given awareness that Indonesia should obey international law.The thing is, beside natural resources greatly contribute to the country development, on the other hand thesustainability of natural resources availability is ignored. The rule of law that should be obey as a ground toexecute the management from economic sector is abandoned as well. The result is there is tendency of rapidlydecline of the capacity environment. Management of natural resources en environmental is not executedproperly with the capacity can affect food crisis. On the management dimension, it is realised that technologicaland industrial based development in order to maintain economic growth usually bring negative effect to theenvironmental,so that threatening sustainability of living things, especially serenity and calmnes humanslife,this is what called as environmental damage caused by human act.